A photo-triggered bioactive nanohydrogel loaded with niobium carbide for stem cell osteogenic differentiation - Ya Li; Yuanzhi Zhang; Derong Xu; Ming Gao; Kunpeng Su; Yingjie Chen; Chen Wang; Xinming Geng; Youchang Liu; Chuanli Zhou; Meng Qiu (Journal of Innovative Optical Health Sciences)
Photo-Cross-Linkable hydrogel has attracted immense interest in the regeneration of bone repair and regeneration strategies due to its superior biocompatibility and tunable mechanical properties. Recently, Nb was reported to strongly promote the bone regeneration process via an accelerated osteoblast-modulated alkaline phosphatase activity mechanism. In particular, Nb2C MXenes have drawn widespread attention due to their excellent biocompatibility and ability to induce bone formation. However, the easy agglomeration of Nb2C nanosheets and subsequent low cell endocytosis efficacy greatly suppressed the osteogenesis effect. In this study, a subtractive nanopore-engineered Nb2C MXene was prepared through a microwave combustion method, gelatin methacrylate was used as the carrier hydrogel, and the photo-triggered Porous-Nb2C@GelMA hydrogel was fabricated by a photo-triggered process. The pore-forming strategy not only successfully improved the distribution of Nb2C and formed more homogenous Porous-Nb2C@GelMA hydrogels but also guided bone marrow mesenchymal stem cells (BMSCs) toward osteoblast differentiation. Porous Nb2C provided convenient cellular grasping and endocytosis for BMSCs, which further created a favorable environment for differentiation and osteogenesis. This, in turn, leads to an increase in the expression of osteogenic markers, such as ALP and ARS, as well as osteogenic factors, such as BMP-2, COL-1, OCN, and OPN. Consequently, enhancing the regenerative microenvironment by incorporating porous Nb2C composite hydrogels shows promise for application in bone regeneration.